Supervisor Recognition, Healthy Interpersonal Relationships, and Work–Life Balance as Determinants of Work Motivation among Police Personnel - Fitria Susanto; Renil Septiano (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines whether supervisor recognition, healthy interpersonal relationships, and work–life balance affect work motivation among personnel of the Directorate of Special Criminal Investigation of the West Sumatra Regional Police. The study used a quantitative explanatory design with a cross-sectional survey approach. The population consisted of 146 personnel, and 82 respondents were obtained through accidental sampling. Data were collected using a five-point Likert questionnaire and analyzed with Partial Least Squares Structural Equation Modeling through SmartPLS 4. The measurement model met the required validity and reliability criteria after one work–life balance indicator was removed. The structural model shows that supervisor recognition has a positive and significant effect on work motivation (β = 0.360; t = 4.395; p < 0.001), healthy interpersonal relationships also have a positive and significant effect and emerge as the strongest predictor (β = 0.411; t = 5.382; p < 0.001), and work–life balance has a positive and significant effect (β = 0.219; t = 2.082; p = 0.037). The model explains 44.0 percent of the variance in work motivation. These findings indicate that work motivation in police organizations is strengthened when recognition, social support, and role balance are managed in an integrated manner.